Vision-related quality of life and visual function in patients undergoing vitrectomy, gas tamponade and cataract surgery for macular hole. Issue 12 (30th June 2009) - Fukuda, S; Okamoto, F; Yuasa, M; Kunikata, T; Okamoto, Y; Hiraoka, T; Oshika, T
Abstract : Aim: To evaluate the relationship between vision-related quality of life (VR-QOL) and visual function in patients undergoing vitrectomy, gas tamponade and cataract surgery for macular hole (MH). Methods: The 25-item National Eye Institute Visual Function Questionnaire (VFQ-25) was self-administered by 32 patients with MH (age 66.2 (SD 5.4) years) preoperatively and at 3 months postoperatively. Clinical data were collected, including logarithm of minimum angle of resolution (logMAR) best corrected visual acuity (BCVA), severity of metamorphopsia and letter contrast sensitivity. The severity of metamorphopsia was evaluated by the M-Charts. MH index was measured using optical coherence tomography. The presence and severity of cataract were graded using the Lens Opacities Classification System III reference standards. Multiple regression analysis was performed to investigate the relationship between various explanatory variables and VFQ-25 questionnaire scores. Explanatory variables tested were the severity of metamorphopsia, visual acuity, letter contrast sensitivity, MH index and grade of cataract. Results: Vitrectomy for MH significantly improved VFQ-25 composite score as well as subscale scores, including general vision, near activities, distance activities, social functioning, mental health and dependency (p<0.05, Wilcoxon signed-rank test). Multiple regression analysis revealed that, both preoperatively and postoperatively, the severity of metamorphopsia had a significant correlation with VFQ-25 composite score (p<0.05), whereas other explanatory variables did not. In addition, changes in the severity of metamorphopsia was the single variable that was significantly related to changes in VFQ-25 composite score (p<0.01). Conclusion: Vitrectomy for MH significantly improved VR-QOL. The severity of metamorphopsia was significantly associated with both preoperative and postoperative VR-QOL.